Improve Reproductive Performance in Your Cow Herd Using Calf Removal - Gary R. Hansen (EDIS)
AN166, a 5-page fact sheet by Gary R. Hansen, discusses three methods of calf-removal and when to use each: short-term calf removal, once-daily suckling, and early weaning. Includes references and tables. Published by the UF Department of Animal Sciences, September 2006.